Counterfactual thinking in psychiatric and neurological diseases: A scoping review. - Sofia Tagini; Federica Solca; Silvia Torre; Agostino Brugnera; Andrea Ciammola; Ketti Mazzocco; Roberta Ferrucci; Vincenzo Silani; Gabriella Pravettoni; Barbara Poletti (PLoS ONE)
Background The ability to simulate alternatives to factual events is called counterfactual thinking (CFT) and it is involved both in emotional and behavioral regulation. CFT deficits have been reported in psychiatric and neurological conditions, possibly contributing to patients' difficulties in modulating behaviors and affections. Thus, acknowledging the presence and possible consequences of CFT impairments might be essential for optimal clinical management. Objectives This scoping review aims to summarize the previous evidence about CFT in psychiatric and neurological diseases to determine the extent of the previous research and what has been discovered so far, the variety of clinical conditions considered, the methodologies adopted, and the relevant issues to be addressed by future investigations. Methods PsycInfo, PubMed, Scopus, and Web of Science were searched to identify articles published up to January 2020, written in English and focused on CFT in adults affected by psychiatric or neurological conditions. Results Twenty-nine studies have been included; most of them focused on psychiatric conditions, a minority considered neurological diseases. The generation of counterfactual thoughts related to a negative real-life or a fictional event and the counterfactual inference test were the most popular tasks adopted. CFT impairments were reported in both psychiatric and neurological conditions, likely associated with a fronto-executive dysfunction. Conclusions Future research might further explore CFT in those psychiatric and neurological conditions in which CFT difficulties have been preliminary reported. Furthermore, it would be recommendable to extend this investigation to all the clinical conditions possibly at risk of fronto-executive dysfunction. In the end, we speculate that since CFT plays a role in driving everyday behaviors, it might be crucial also when medical decisions are involved; thus, future research might extend the investigation of CFT especially to those populations that implicate complex clinical management.